Acute infectious diseases and immunologic responses. Some stories from clinical practice apropos the Influenza A (H1N1) pandemic - Alfredo Darío Espinosa Brito (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2011)
Apropos of the appearance of some unusual clinical pictures in the course of the recent epidemic of Influenza A (H1N1), and with the intention of sharing controversial ideas related to the immunologic responses of the patients to the infectious agents, we expose here a group of stories arisen from a clinical practice of almost five decades.